2021
DOI: 10.4025/actascianimsci.v44i1.53382
|View full text |Cite
|
Sign up to set email alerts
|

Different sieving methods for determining the physical characteristics in ground corn

Abstract: We evaluated various sieving methods to estimate particle size (PS) and geometric standard deviation (GSD) of ground corn. The corn had been previously divided in six fractions and each one ground in a hammermill (1-, 2-, 3-, 4-, 5- or 12-mm sieves). The stacked sieving method, with prior drying at 105ºC without agitators was the reference. We evaluated eight sieving methods, distributed in a factorial design (2 x 2 x 2 x 6), consisting of the following treatments: i) with and without agitators (two 25-mm rubb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(23 reference statements)
0
2
0
1
Order By: Relevance
“…26 Wet screening of coal has also shown lower efficiency in comparison with dry screening. 59 Biazzi et al also observed that moisture reduces the sieving efficiency of ground maize and proposed pre-drying, 60 and the same was detected by Siliveru and Ambrose using flour samples with 10% and 14% of moisture from both hard and soft winter wheat. 27 On the other hand, Liu found that when the moisture of soft wheat flour increased from 7% to 11%, more fine particles were sifted through the sieve.…”
Section: And 3 H)mentioning
confidence: 65%
“…26 Wet screening of coal has also shown lower efficiency in comparison with dry screening. 59 Biazzi et al also observed that moisture reduces the sieving efficiency of ground maize and proposed pre-drying, 60 and the same was detected by Siliveru and Ambrose using flour samples with 10% and 14% of moisture from both hard and soft winter wheat. 27 On the other hand, Liu found that when the moisture of soft wheat flour increased from 7% to 11%, more fine particles were sifted through the sieve.…”
Section: And 3 H)mentioning
confidence: 65%
“…The separation method by sieving is a method commonly used to separate large (macro) particles or particles that have a large molecular weight (Biazzi, et al, 2022). In this case, elementary sulphur solids which have a large molecular weight can be separated from produced water during filtration phase with sieving method.…”
Section: Bsru Bwtu Atumentioning
confidence: 99%
“…Ayakan pada uji gradasi ayakan digunakan untuk memisahkan tanah kasar dan halus agar bisa menentukan butiran tanah lempung yang sesuai dengan berat tanah yang lolos dan tertahan pada setiap ukuran ayakan. Ayakan yang digunakan dalam pegujian ini adalah nomor 4, 10, 20, 3, 50, 100, dan 200 (Biazzi et al, 2022).…”
Section: Alat Penelitian Uji Gradasi Ayakan Ayakanunclassified